1970
DOI: 10.1254/jjp.20.530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ouabain and 2,4-Dinitrophenol on Calcium Distribution and Exchange in Guinea Pig Taenia Coli in High-Potassium Solution

Abstract: Previous studies have shown that Ca influx increased but Ca efflux did not change during the contracture of taenia coli induced in hypertonically added 40 mm potassium solution (1) and the results were supported by the others (2-6). Further, the movements of Ca in the muscle in high-K solution might be differently affected by ouabain and 2, 4-dinitrophenol during the abolition of the tonic tension by them (6, 7).The experiments reported here were carried out in purpose to find the nature of Ca distribution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1971
1971
1982
1982

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
(23 reference statements)
2
7
0
Order By: Relevance
“…on the smooth muscles in the presence of various stimulants and relaxants. However, the presence of the correlation between tension development and the size of TBF has al ready been suggested (3)(4)(5) and the present data also supports this.…”
Section: Tensionsupporting
confidence: 85%
See 1 more Smart Citation
“…on the smooth muscles in the presence of various stimulants and relaxants. However, the presence of the correlation between tension development and the size of TBF has al ready been suggested (3)(4)(5) and the present data also supports this.…”
Section: Tensionsupporting
confidence: 85%
“…However, as reviewed by L&uuml;llmann (1), no correlation has been found between tissue Ca content or Ca fluxes and the contractile response of the smooth muscle to various stimu lants.<BR> In guinea pig taenia coli, it was shown that cellular Ca fraction of relatively tightly bound form increase during contraction induced by barium or high concentration of potas sium and decreased during the abolition of tension development by various inhibiting factors, and suggested that the shift of Ca into the relatively tightly bound fraction with in the cell might have a concern with the tension development (2)(3)(4)(5).<BR>…”
mentioning
confidence: 99%
“…Previous studies have shown that the tonic contraction produced by a high-K solution is inhibited by ouabain in the guinea-pig taenia coli (2,(19)(20)(21)(22)(23)(24) and ileum (25). In the present paper, we have found that the effects of ouabain on K-contraction are different in several smooth muscle tissues isolated only from the guinea-pig.…”
Section: Discussionsupporting
confidence: 47%
“…The size of TBF increased during tonic contraction induced by carbachol, pilocarpine (3), histamine (4), barium (5) and 40 mM potassium (5,6), and decreased during abolition of tension by specific antagonists oft he stimulants (3,4), metabolic inhibiting factors and factors inhibiting active Na transport (8,9). from these data., it was suggested that the increase in the size of TBF, i.e., a shift of cellular Ca to a more slowly exchangeable fraction, could be related to contraction of smooth muscle, and the movement of Ca related to metabolism.<BR>…”
mentioning
confidence: 80%